Poverty alleviation and consumption smoothing in european pension systems: convergence or divergence? - Chybalski, Filip (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
Since pension systems have undergone reforms due to ageing populations, some changes linked to the relations between the objectives of pensions may also be expected. The two main social goals of pensions are poverty relief and consumption smoothing. In this paper the relationship between these two goals in 30 European countries using Eurostat data for the years 2007-2013 is investigated. Two different poverty measures: the at-risk-of-poverty rate and severe material deprivation ratio, and two different measures reflecting consumption smoothing: aggregate replacement ratio and relative median income ratio, are used. The method employed in the analysis is based mostly on the regression models for cross-section and panel data, however trend analysis and correlation analysis are also implemented. The results of the study suggest that despite deteriorating demographics and pension finance sustainability, the two analysed objectives seem to be still more convergent than divergent. In the majority of the studied countries, measures reflecting poverty are positively correlated with measures reflecting consumption smoothing. The other interesting conclusion is that there are many countries where relative poverty is not correlated with absolute poverty, or is even negatively correlated, which means that these two types of poverty may be quite different phenomena. This is probably caused by the ineffective redistribution which supports to a greater extent poor people instead of the poorest. The results also suggest that today’s workers are paying for the generosity of pension systems, therefore intergenerational redistribution may be a more important tool to ensure adequate pensions than an intragenerational one
Argumenta Oeconomica, 2018, Nr 1 (40), s. 181-202
Keywords: pension; retirement; consumption smoothing; poverty; redistribution; income